UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA KELAS XI DI MA BABUL FUTUH PANDAAN - Ayu Wulandari; Ika Ratih Sulistiani; Adi Sudrajat (VICRATINA, 2021)
The teaching andilearning process, Islamic education teachers play a very importanirole in student  success, Therefore, Islamic education teachers must know what steps to take first to deal with students in learning and teaching process. The learningiachievementsiof Islamicireligious educationican beiimproved through increasingilearning motivation. Focus of research is to discuss planning, strategy and stepito upgradeiincrease learning motivation To achieve this goal, itheiresearcher uses a qualitative approachibased on phenomenology byiusing case study research.. Thisistudy destination to describe and analyze of Islamic education teachersiin upgradeimotivation student at islamic Senior High School Babul Futuh Pandaan, and the results of improving students at Islamic Senior High School Babul Futuh Pandaan. From theiresults of research at Madrasah Aliyah Babul Futuh Pandaan, it canibe concluded knowing how the effortsimadeiby teachers in increasing students learning motivation at high school Babul Futuh Pandaan that in learning has not been successful because it is influenced by internal factors, namely within the students themselvesiand external factors, namely there is no good cooperation between the educationisector and the parents of students that can affectistudents learning motivation. Kata Kunci: Teacher Effort. Motivation, Islamic Education. i